KARAKTERISTIK PETANI BERLAHAN SEMPIT DI DESA TOLOK KECAMATAN TOMPASO - Miranda Mandang; Mex Frans Lodwyk Sondakh; Olly Esry Harryani Laoh (Sam Ratulangi University, 2020)
This study aims to determine the characteristics of smallholder farmers in Tolok Village, Tompaso District. The study was conducted in August to September 2019. The selection of samples in this study was carried out purposevley with 33 respondent farmers, namely those who have small size of land of less than 0.5 hectares. The data used in this study are primary data and secondary data. Primary data collected through interviews and observations. Secondary data were obtained from the Tolok Village office, library and the Internet. Data analysis uses description analysis, which describes the characteristics of smallholder farmers and is presented in tabular form. The results showed that farmers who have small size of land with low income and are unable to rely solely on the agricultural sector as a source of income. The non-agricultural sector is also used as a source of additional income to meet their needs.*eprm*